“Efecto del fluazifop butil en el control post-emergente de arrogillo (rottboellia exaltata), y en el rendimiento de gaupi (vigna unguiculata) en el Bajo Mayo” - Garcia Armas, Alfonso (2001)
In- r:he present experiment; was ' dnben in tbe Sector -uritohuasi on: the District oii JuarfGiiéfri "'· · Provine e and Departament of San Martfn, in exempt texture soil. with pH of 7, 72, mean fetility with type of tropical diy furest, a rainfaill of 1 047 nun/year and an average temperature of 26,3 ºC. The objetives of the present investigation work were measured the efect of the diferen dose of the herbicide Fluamop applied in pulverization to 25 and 50 days after the sowing; their bis action .fitotoxic to tbe cultivation of cowpea; the degree of control of undergrowtbs; their incidence on the grain yieldand to make the económic analysis of the treatments througb the relationship benefit/cost The statistic design utlised was tbe block designs thoroughly randomiced with 9 treatmentsand 4 repetitions. The ñtitoxic e:ffect was evaluated to 4 and 5 days after the aplication, no obtaining toxicity sorne to the cultivation; for the degree of control of oodergrowths was evaluated to 6 and 7 days the aplications, being obtained an ex:cellent control; for the evaluation of the e:ffect :fitotoxic and the degree of control of tmdergrowths used the scale "Euopean Weed Research Council"(EWRC). Olso its necessaxy to mention that was achíeved the yield but hig with the aplication of 4 1 p.c.lha (2 I to 25 d.ds. and 2 l to 50 dds.). with 1 660 Kgfba. Also according to the cost and the economic analysis was obtained a grater usefulness with the trea1ment 2 (SI. 815,25 soles oro/ha). anda relationship cost bene:fit of0.45.